2011
DOI: 10.1007/s12016-010-8230-2
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus and Atopic Dermatitis

Abstract: Atopic eczema is one of the most pruritic skin diseases. Mediators of atopic eczema itch in the skin are still mostly unknown, but recent studies showed that the histamine 4 receptor plays an important role in itch pathophysiology; tryptase and interleukin-31 are also involved. Differences in itch perception and itch kinetics between healthy volunteers and eczema patients point towards an ongoing central nervous inhibitory activity in patients. Questionnaire studies reported comparatively higher loads in affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 65 publications
1
28
0
5
Order By: Relevance
“…IL-31 is an inducer of pruritus found to be correlated with SCORAD index and subjective sleeplessness in children with AD. 46 We found that the serum levels of IL-31 and serotonin, another inducer of pruritus, 47,48 were associated with a change in sleep architecture. Further studies are warranted to substantiate these exploratory findings.…”
Section: Figurementioning
confidence: 88%
“…IL-31 is an inducer of pruritus found to be correlated with SCORAD index and subjective sleeplessness in children with AD. 46 We found that the serum levels of IL-31 and serotonin, another inducer of pruritus, 47,48 were associated with a change in sleep architecture. Further studies are warranted to substantiate these exploratory findings.…”
Section: Figurementioning
confidence: 88%
“…The pathophysiology behind pruritus is complex, and both peripheral and central factors are involved. 51 Examples of peripheral factors are irritant entry through a defective epidermal barrier, transepidermal water loss, and protease activity in the skin. 52 Centrally, there is a complex interplay of multiple different mediators, although histamine seems to have a limited role, if any.…”
Section: Itch Controlmentioning
confidence: 99%
“…Those patients in whom first-line treatment fails are often graduated to topical corticosteroids, calcineurin inhibitors or systemic immunomodulatory therapies [127]. Since pruritus is often associated with AD, antihistamines have also been prescribed [128,129].…”
Section: Pde4 Inhibitors In the Treatment Of Atopic Dermatitismentioning
confidence: 99%